Association of Mitochondrial Variants with the Joint Occurrence of Polycystic Ovary Syndrome and Hashimoto's Thyroiditis - Natalia Zeber-Lubecka; Maria Kulecka; Katarzyna Suchta; Michalina Dąbrowska; Michał Ciebiera; Ewa E. Hennig (MDPI AG, 2023)
Background. The prevalence of Hashimoto's thyroiditis (HT) among women with polycystic ovary syndrome (PCOS) is higher than in the general female population, but the factors predisposing to the coexistence of these disorders remain unclear. This study employed whole genome sequencing of mitochondrial DNA to identify genetic variants potentially associated with the development of PCOS and HT and predisposing to their joint occurrence. Results. A total of 84 women participated, including patients with PCOS, HT, coexisting PCOS and HT (PCOS + HT) and healthy women. Both Fisher's exact and Mann-Whitney U statistical analyses were performed to compare the frequency of variants between groups. Ten differentiating variants were common to both analyses in PCOS + HT vs. PCOS, one in PCOS + HT vs. HT, and six in PCOS + HT vs. control. Several variants differentiating the PCOS + HT group from PCOS and controls were identified, located both in the mitochondrial genes (including the MT-CYB, MT-ND1, MT-ND2, MT-ND4, MT-ND6, MT-CO1, MT-CO3) and the D-loop region. Only two variants differentiated PCOS + HT and HT groups. One variant (13237a in MT-ND5) was common for all three comparisons and underrepresented in the PCOS + HT group. Functional enrichment analysis showed 10 pathways that were unique for the comparison of PCOS + HT and PCOS groups, especially related to ATP production and oxidative phosphorylation, and one pathway, the NADH-quinone oxidoreductase, chain M/4, that was unique for the comparison of PCOS + HT and control groups. Notably, nine pathways shared commonality between PCOS + HT vs. PCOS and PCOS + HT vs. control, related to the biogenesis and assembly of Complex I. Conclusion. This study provides novel insights into the genetic variants associated with oxidative stress in women with coexisting PCOS and HT. Mitochondrial dysfunction and oxidative stress appear to play a role in the pathogenesis of both conditions. However, more mitochondrial variants were found to differentiate women with both PCOS and HT from those with PCOS alone than from those with HT alone.